Political Economy of the Social Credit Movement - Stoyanov, Petar (Research Papers, 2018)
In times of crisis and recession conventional economic thought usually starts to lose its value in favor of unorthodox thinkers for solutions. Giving the pressing severity of unsolved socio-economic problems this paper analyses the ideas and contributions of the great British engineer, and political economist Clifford Hugh Douglas. Clarifying the reasons why he has been misunderstood, ignored, and even censored, his theories concerning money, debt, deficiency of purchasing power and economic democracy are presented and opposed to the dominant schools of economic thought.
Keywords: Social credit; Chronic deficiency of purchasing power; Unpayable debt